Research of femtocell technologies for mobile cellular networks - Pasarelski, Rosen; Pasarelska, Teodora (Yearbook Telecommunications, 2022)
The purpose of writing this article is to present and study femtocellular technologies for mobile cellular networks. With the introduction of the fourth 4G-LTE and the fifth 5G generation of mobile cellular systems, the term femto cell began to be strongly mentioned. Femto cells are very small cells that provide mobile service users with a home base station to connect to the telecommunications operator's network. The femtocell technologies are mainly looking for ever higher data rates indoors, which most often leads to the implementation of UMTS / HSPA modules in the femtocell access point, as well as LTE and 5G.